Renal histopathological lesions after liver transplantation: What can we find besides calcineurin inhibitor-induced nephrotoxicity? - Haijiao Jin; Yuehan Wei; Yongbing Qian; Jiang Zhang; Yao Xu; Hang Zhou; Minfang Zhang; Wenyan Zhou; Chaojun Qi; Wei Jin; Shan Mou; Qin Wang; et al. (BMC Nephrology, 2022)
Abstract Background Chronic kidney disease (CKD) is a common complication after liver transplantation and is traditionally considered to be secondary to calcineurin inhibitors (CNIs). However, several studies have reported that the etiology of CKD after liver transplantation is broad and may only be assessed accurately by renal biopsy. The current study aimed to explore the usefulness of renal biopsies in managing CKD after liver transplantation in daily clinical practice. Method This retrospective analysis enrolled all post-liver transplantation patients who had a renal biopsy in a single center from July 2018 to February 2021. Results Fourteen renal biopsies were retrieved for review from 14 patients at a median of 35.7 (minimum-maximum: 2.80–134.73) months following liver transplantation. The male-to-female ratio was 13:1 (age range, 31–75 years). The histomorphological alterations were varied. The predominant glomerular histomorphological changes included focal segmental glomerular sclerosis (FSGS) (n = 4), diabetic glomerulopathy (n = 4), and membranoproliferative glomerulonephritis (n = 4). Thirteen (92.9%) patients had renal arteriolar sclerosis. Immune complex nephritis was present in six patients, of whom only two had abnormal serum immunological indicators. Despite interstitial fibrosis and tubular atrophy being present in all the patients, only six (42.9%) presented with severe interstitial injury. No major renal biopsy-related complications occurred. After a mean follow-up of 11.8 months (range: 1.2–29.8), three patients progressed to end-stage renal disease (ESRD). Conclusion The etiology of CKD after liver transplantation might be more complex than originally thought and should not be diagnosed simply as calcineurin inhibitors(CNI)-related nephropathy. Renal biopsy plays a potentially important role in the diagnosis and treatment of CKD after liver transplantation and might not be fully substituted by urine or blood tests. It may help avoid unnecessary changes to the immunosuppressants and inadequate treatment of primary diseases.